2017
DOI: 10.1186/s13018-017-0632-x
|View full text |Cite
|
Sign up to set email alerts
|

Eight orthopedic surgeons achieved moderate to excellent reliability measuring the preoperative posterior tilt angle in 50 Garden-I and Garden-II femoral neck fractures

Abstract: BackgroundStudies of elderly patients with Garden-I and Garden-II femoral neck fractures (FNFs) suggest that a preoperative posterior tilt of the femoral head of at least 20° increases the risk of fixation failure. A recently published treatment algorithm recommended hemiarthroplasty over internal fixation for elderly patients with Garden-I and Garden-II FNFs and a preoperative posterior tilt of at least 20°. However, the reliability of the method used to measure the posterior tilt has not been assessed accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…We did not perform any validation of the measurements; however, the inter- and intra-rater reliability of posterior tilt measurements in cases of minimally displaced FNFs has previously been reported to be excellent although the repeatability and agreement by the minimal detectable change were found to be 14° (Palm et al. 2009, Dolatowski and Hoelsbrekken 2017).…”
Section: Discussionmentioning
confidence: 97%
“…We did not perform any validation of the measurements; however, the inter- and intra-rater reliability of posterior tilt measurements in cases of minimally displaced FNFs has previously been reported to be excellent although the repeatability and agreement by the minimal detectable change were found to be 14° (Palm et al. 2009, Dolatowski and Hoelsbrekken 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Two studies have indicated that a posterior tilt of >20° is associated with an increased risk of fixation failure 2,3 , but those findings have been contested by the authors of a third study 17 . The conflicting results could possibly be explained by measurements having poor reliability, but the reliability has been reported to be moderate to excellent 2,4 . It is therefore unlikely that low reliability is the cause of the observed inconsistencies, which underlines the importance of determining the validity of the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…CT images were compared with the corresponding radiographs, but minor changes are difficult to evaluate and we cannot exclude the possibility of a change occurring between CT scans and radiographic examinations. We also did not assess the reliability of the measurements used in the present study, but we previously evaluated both test-retest and intertester reliability of these measurements 4,9 . The measurements were all found to be acceptable, with the exception of femoral head rotation in 3D models 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The femoral neck fractures are classified into Garden type I and II (NDFNFs) and Garden type III and IV (displaced femoral neck fractures) (Table 1 ). The NDFNFs are prone to re-displacement, resulting in a fracture healing rate of 44.3% and a postoperative re-displacement rate of 33% to 44% [ 3 , 4 ]. Therefore, surgical treatments may be a better option for the elderly [ 5 ].…”
Section: Introductionmentioning
confidence: 99%